LIMITING THE VERTICAL VARIANCE OF ANNUAL RING AREA OF POPULUS NIGRA PLANTATION IN NINEVAH - Muzahem Younis (Mesopotamia Journal of Agriculture)
Limitation of annual ring area along the extension of the principle stalk has an important role in the estimation of the quantity and quality of stalk wooden segments, The thickness of the ring distribution inside the stem is correlated to the wood density, which in turn related to the physical and chemical characteristics of tree wooden stalk. More over it could be explaining the translocation along the bole estimated of annual ring area at any location . it is very important for the forest management to table discern manger related with siliviculture activities, which apply in the forest, for this reason, we chose (12) tree of populous nigra grown normally in the forest plantation of Nineveh. The selected samples were of deferent ages and density. Stem analysis using to obtain the data for tree, by using the filed and stem analysis data and different available regression method within stat Graf program system, and it became possible to prepare forecasting equation of vertical distribution area. This involved different regression methods depending on statistical analysis scales in evaluation the equation and the result equation is as follows: S= b0 + b1(hb2/Ab3) R2= 0.77 S.E% = 0.73 Determination of equation coefficients and standard error show accurate values, also the equation were tested by taking standardized residual. The model is accurately describe the fluctuation of cross-sectional area increment along tree stem from the top to ground level, and it is possible to represent the ring area by curve which could be segmented into two parts, initially increasing part, which is looked as an s-shaped with infection point, while the second part is linear and the third part with an exponential shape which describe the stem portion of the base. A table has been prepared representing the annual ring thickness for any height level and annual growth of the tree for any age of different densities.